A Visual Approach for the Definition of Behavior in Environments for Internet of Things - Junior, Namedin; Souto, Eduardo; Sousa, Wesllen; Nascimento, Rogério P. C. do; Aschoff, Rafael (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
Internet of Things (IoT) describes how the world, where daily-live objects are connected to the Internet, is increasingly present in people’s lives. However, actual solutions that enable the IoT are designed to be used only by IT experts. This article proposes a Behavior Definition Model for IoT EcoSystems (BDM4IoT), a model designed to enable non-IT experts to easily design and configure the behavior of their own environments for IoT according to their needs. The validation of the proposed model is carried out through a graphical modeling tool called Êxodo GUI, which allows users to easily configure, manipulate and create behavioral models using BDM4IoT. The obtained results prove the viability of this approach for the inclusion of non-IT experts in the creative and managerial IoT process.